Pengaruh Metode Blended Learning dalam Peningkatan Pengetahuan Sumber Daya Manusia Kesehatan di Puskesmas Sulawesi Utara - Lolong, Rima; Rotty, Viktory Nicodemus Joufree; Tambingon, Henny Nikolin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Introduction: Blended learning is a combination or combination of various learning both distance and face-to-face. Blended learning is believed to increase students' knowledge. Therefore, the application of blended learning in health human resource (HR) training needs to be done. The purpose of this study is to analyze the effect of the blended learning method in training on increasing the knowledge of human resources in Puskesmas in North Sulawesi. Method: This is a quasi-experimental research with one group pre-posttest approach. This research was carried out at the Regional Technical Implementation Unit (UPTD) of the Health Training Center of the Regional Health Office of North Sulawesi Province on 5-10 September 2022. The respondents of this study were 30 Health Human Resources, namely the Rapid Action Team for Overcoming Outbreaks and Outbreaks at the Puskesmas . The variable measured in this study is the level of knowledge. The instrument used is a questionnaire. Data analysis carried out in this study is univariate and bivariate analysis. Results: The results showed that there is an increase in both the lowest, highest and average values. The lowest value increased by 48.5 points, the highest value increased by 30 points and the average value increased by 33.33 points. The t-test results show that the t-value is 20.0478 and the p-value is 0.0001 (p<0.05). These values indicate a difference in knowledge before and after being given training with the blended learning method. Conclusion: It can be concluded that the effect of training with the blended learning method on the knowledge of the trainees